Efficacy of probiotic supplements in the treatment of sarcopenia: A systematic review and meta-analysis. - Yi Wang; Ping Lei (PLoS ONE)
Although some studies have confirmed the efficacy of probiotics in the treatment of sarcopenia, the intervention of sarcopenia is a comprehensive consideration of many factors, and the efficacy of probiotics is still controversial. Therefore, this study systematically evaluated the efficacy of probiotics in the intervention of sarcopenia via high-quality meta-analysis, providing a basis for the clinical diagnosis and treatment of sarcopenia. Randomized controlled trials related to probiotics in the treatment of sarcopenia were searched in PubMed, Embase, the Cochrane Library and Web of Science. The search time was from inception to 2024-07-17. Two investigators independently screened the articles, extracted data, and assessed the risk of bias of the included studies. Meta-analysis was performed using RevMan 5.4 and Stata 14.0 software. A total of 22 eligible studies were included. The results showed that there was no statistically significant difference between probiotics and placebo in improving muscle mass and Lean body mass in sarcopenia patients; MD: 0.66, 95%CI: - 0.01-1.33; Z = 1.93, P > 0.05; MD: - 0.13, 95%CI: -0.81-0.55; Z = 0.38, P = 0.71 > 0.05. However, probiotics were found to significantly improve overall muscle strength compared with the placebo group. MD: 2.99, 95%CI: 2.14-3.85; Z = 6.86, P < 0.001. Probiotics can significantly improve global muscle strength in patients with sarcopenia. It is suggested that probiotics have certain clinical value in the clinical treatment of sarcopenia, but the results may be limited by the number and quality of included studies. The above conclusions need to be verified by more high-quality studies.